2009
DOI: 10.1007/s10236-009-0180-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of partial steps and momentum advection schemes in a global ocean circulation model at eddy-permitting resolution

Abstract: The original version of this article unfortunately contained a mistake. The sequence of first and last name of Bernard Barnier was incorrect. The correct sequence is given above.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
429
0
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 323 publications
(435 citation statements)
references
References 0 publications
5
429
0
1
Order By: Relevance
“…The wide range of densities associated with this AMOC variability peak suggests that the associated circulation fluctuations have a barotropic character, as indeed is expected within strong recirculations observed off the U.S. coast (e.g., Bryden et al 2009). On the other hand, our two 1 /48 simulations, like many eddy-permitting model solutions, exhibit an unrealistic, almost standing eddy near Cape Hatteras (see, e.g., Barnier et al 2006); whether this half-intrinsic AMOC variability peak is robust and realistic is therefore questionable.…”
Section: Total and Intrinsic Amoc Variability At Interannual-to-decadmentioning
confidence: 77%
See 1 more Smart Citation
“…The wide range of densities associated with this AMOC variability peak suggests that the associated circulation fluctuations have a barotropic character, as indeed is expected within strong recirculations observed off the U.S. coast (e.g., Bryden et al 2009). On the other hand, our two 1 /48 simulations, like many eddy-permitting model solutions, exhibit an unrealistic, almost standing eddy near Cape Hatteras (see, e.g., Barnier et al 2006); whether this half-intrinsic AMOC variability peak is robust and realistic is therefore questionable.…”
Section: Total and Intrinsic Amoc Variability At Interannual-to-decadmentioning
confidence: 77%
“…The six simulations share a partial cell representation of topography and a momentum advection scheme that conserves energy and enstrophy (Barnier et al 2006;Penduff et al 2007;Le Sommer et al 2009); a total variance diminishing (TVD) tracer advection scheme; an isopycnal Laplacian tracer diffusion operator; a vertical mixing scheme based on the TKE turbulent closure model (Blanke and Delecluse 1993); and a convective adjustment scheme based on enhanced vertical mixing in case of static instability. Table 1 summarizes the main differences between these simulations.…”
Section: A Model Simulationsmentioning
confidence: 99%
“…The vertical layer thickness is 6 m near the ocean surface and increases with depths. A partialcell approach is used for the bottom cell (Barnier et al, 2006). Especially in the subpolar North Atlantic it has been demonstrated that this leads to an improved boundary current circulation (Käse et al, 2001).…”
Section: ) Viking20 -High-resolution Modeling Of the Subpolar North mentioning
confidence: 99%
“…The total vorticity term is discretised by an adaptation of the scheme 21 referred to as the energy-enstrophy conserving (EEN) scheme that conserves both total energy and potential enstrophy. 22 The model domain covers the North Atlantic basin from 208S to 708N and from 98.58W to 208E, with a horizontal resolution of 1/38 x 1/38 cosine (latitude). The vertical discretisation has 42 geopotential levels, with a grid spacing that increases from 12m at the surface to 200m below 1500m depth.…”
Section: Introductionmentioning
confidence: 99%
“…15,16,27 Note that this scheme is also being developed in a pre-operational mode for the main MO operational prototypes recently based on the NEMO-OPA code 19 which has a free-surface and for which some significant numerical improvements have been made. 22 The SAM2v1 assimilation scheme is a multivariate assimilation algorithm consisting of a SEEK (Singular Evolutive Extended Kalman) filter. 28 The SEEK filter is a reduced-order Kalman filter introduced by Pham et al 29 in the context of mesoscale ocean models and has been designed for a large variety of basin-scale ocean models and validated in many studies.…”
Section: Introductionmentioning
confidence: 99%